Functional, immunological and three-dimensional analysis of chemically synthesisedsporozoite peptides as components of a fully-effective antimalarial vaccine (2011)
Our ongoing search for a fully-effective vaccine against the Plasmodium falciparum parasite (causing the most lethal form ofhuman malaria) has been focused on identifying and characterising proteins' amino acid sequences (high activity binding peptides orHABPs) involved in parasite invasion of red blood cells (RBC) by the merozoite and hepatocytes by the sporozoite. Many such merozoiteHABPs have been recognised and molecularly and structurally characterised; however, native HABPs are immunologically silentsince they do not induce any immune response or protection against P. falciparum malaria infection and they have to be structurallymodified to allow them to fit perfectly into immune system molecules.A deeply structural analysis of these conserved merozoite HABPs and their modified analogues has led to rules or principles becomingrecognised for constructing a logical and rational methodology for a minimal subunit-based, multi-epitope, multi-stage, chemicallysynthesisedvaccine. The same in-depth analysis of the most relevant sporozoite proteins involved in sporozoite cell-traversal and hepatocyteinvasion as well as the hepatic stage is shown here.Specifically modifying these HABPs has resulted in a new set of potential pre-erythrocyte targets which are able to induce high, longlastingantibody titres in Aotus monkeys, against their corresponding recombinant proteins and the complete parasite native molecules.This review shows how these rules may be applied against the first stage of parasite invasion (i.e. the sporozoite) to mount the first line ofdefence against the malarial parasite, which may indeed be the most effective one. Our results strongly support including some of thesemodified sporozoite HABPs in combination with the previously-described modified merozoite HABPs for obtaining the aforementionedfully-protective, multiepitope, multi-stage, minimal subunit-based, chemically-synthesized, antimalarial vaccine. © 2011 Bentham Science Publishers.